Online courses for information literacy skills development in VIA University college - Schneider, Maria Viftrup (Septentrio Conference Series, 2021)
In order to address a need for skills development regarding reference management and literature searching in teaching staff, IT and Library teamed up to design a series of online courses. The library approach was to design courses that could also support library intruction for our students, since this is the larger target group of the library, and their needs to a large extent is simular to those of staff. Courses applicable to ongoing library instruction and flipped classroom, was designed to meet the need of the general student/staff, in order to be relevant for the largest number of VIAs faculties. Our four online courses on reference mangement and literature searching is superior to alternatives in regard of the Danish language and the match to local context in terms of platforms and electronic library ressources. Also the courses are built in to the organizational LMS alongside a range of other online courses, and therefore easy to find for our users. The courses are also accessable on the OER library platform www.learninglib.dk.The usage is very much dependant of the attachment to faculty education lectures and to the impact on - and assessment of - student performance. By the end of the first year half of the library staff reported to have been refering students to the courses verbally during instruction, and a quarter of staff had been refering in writing by mail or LMS.More than half had refered to one Zotero video, and a third to a video from the course Literature searching 1. We hope to se these numbers increased when we repeat the survey this winter.